Inputs of humic fluorescent dissolved organic matter via submarine groundwater discharge to coastal waters off a volcanic island (Jeju, Korea) - Jeonghyun Kim (Nature Portfolio, 2017)
Abstract The abundance of fluorescent dissolved organic matter (FDOM) in the surface ocean plays a critical role in the growth of marine microorganisms and corals by affecting the optical properties (i.e., the penetration of UV radiation) of seawater. In general, it is known that rivers are the main source of FDOM to surface ocean waters. Here, however, we show that the concentrations of FDOM in coastal seawater off a volcanic island, Jeju, Korea, are dependent primarily on submarine groundwater discharge (SGD). Based on a significant correlation between 222Rn and salinity in seawater, fresh groundwater was found to be the main source of groundwater as well as fresh water in the bay. The addition of dissolved organic carbon (DOC) and protein-like FDOM to the bay via SGD was generally negligible or negative. However, SGD enhanced the inventory of humic-like FDOM (FDOMH) in seawater by 2–3 times over all seasons, with conservative behavior of FDOMH in bay seawater. These results suggest that SGD-driven fluxes of FDOM regulate its inventory in seawater and consequently play a significant role in determining the optical properties of coastal waters off islands and associated coastal ecosystems (i.e., corals).